Neurodegeneration Within the Amygdala Is Differentially Induced by Opioid and HIV-1 Tat Exposure - Nass, Sara R.; Ohene-Nyako, Michael; Hahn, Yun K.; Knapp, Pamela E.; Hauser, Kurt F. (Frontiers in Neuroscience, 2022)
Opioid use disorder (OUD) is a critical problem that contributes to the spread of HIV and may intrinsically worsen neuroHIV. Despite the advent of combined antiretroviral therapies (cART), about half of persons infected with HIV (PWH) experience cognitive and emotional deficits that can be exacerbated by opioid abuse. HIV-1 Tat is expressed in the central nervous system (CNS) of PWH on cART and is thought to contribute to neuroHIV. The amygdala regulates emotion and memories associated with fear and stress and is important in addiction behavior. Notwithstanding its importance in emotional saliency, the effects of HIV and opioids in the amygdala are underexplored. To assess Tat- and morphine-induced neuropathology within the amygdala, Male Tat transgenic (tg) mice were exposed to Tat for 8 weeks and administered saline and/or escalating doses of morphine twice daily (s.c.) during the last 2 weeks of Tat exposure. Eight weeks of Tat exposure decreased the acoustic startle response and the dendritic spine density in the basolateral amygdala, but not the central nucleus of the amygdala. In contrast, repeated exposure to morphine alone, but not Tat, increased the acoustic startle response and whole amygdalar levels of Aβ monomers and oligomers and tau phosphorylation at Ser396, but not neurofilament light chain levels. Co-exposure to Tat and morphine decreased habituation and prepulse inhibition to the acoustic startle response and potentiated the morphine-induced increase in Aβ monomers. Together, our findings indicate that sustained Tat and morphine exposure differentially promote synaptodendritic degeneration within the amygdala and alter sensorimotor processing.